PENGARUH DESAIN KAWASAN TERHADAP WALKABILITY WISATAWAN DI JALAN PRAWIROTAMAN â TIRTODIPURAN YOGYAKARTA - , BONIFASIA YUNIAR RIFANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Walking is simple, free, and the easiest way for tourists to explore neighborhood or discover city. Walking as a physical activity has been widely related to built environment, such as urban design. In this research, the term of urban design refers to physical features on Prawirotaman dan Tirtodipuran Streets that consist of four elements: pedestrian facilities